Lightweight concrete using oil palm shells as aggregates. - Abdus Salam, S.K.; Abang Ali , Abang Abdullah (1985)
Much effort is being made to increase palm oil production in view of its economic importance,at the same time technologists are concerned with efficient utilization of the milling by-products e.g.,sludge,kernels,fibres and shells. Though the palm oil shell produced is mainly used as fuel for the boiler,occasionally it is used for paving farm roads or sold commercially. The shell is hard and does not easily suffer deterioration. Since its density is only 550 to 650kg/cu.m it can be profitably used as a substitute for gravel in making concrete and the resulting concrete will be lightweight in nature and at the same time structurally sound. The dead load of a structure can be a high proportion of the total load. Therefore the reduction in weight of the structure by using lightweight concrete may result in lighter sections and reduction in the cost of foundations achieving the final economy of the total structure. Lightweight concretes have better insulation properties and a reduction in the cost of heating or cooling is possible. The present study has been concentrated on the development of lightweight concrete using palm oil shell as the coarse aggregate replacing the gravel aggregate in the normal concrete making for rural housing.